An analysis of young students' thinking when completing basic coding tasks using Scratch Jnr. On the iPad - Falloon, G. (Journal of computer assisted learning, 2016)
Recent government moves in many countries have seen coding included in school curricula, or promoted as part of computing, mathematics or science programmes. While these moves have generally been associated with a need to engage more young people in technology study, research has hinted at possible benefits from learning to program including fostering general thinking skills. However, little research has been carried out exploring these ideas. This study analysed data collected while 5‐ and 6‐year‐old students in a New Zealand primary school were using Scratch Jnr. to learn about basic shapes, as part of a numeracy topic. Analysis combined Brennan and Resnick's (2012) computational thinking skills framework and Krathwohl's (2002) revision of Bloom's Taxonomy to evaluate any role general thinking skills played in these students' coding work. Results suggest including basic coding in primary curricula provides teachers with an effective means of exercising their students' general and higher order thinking skills. They build on Brennan and Resnick's (2012) framework by including conceptualization as an important element in students' computational work and highlight the role of predictive thinking in debugging code. Findings support historical arguments that more needs to be done to investigate students' cognitive processes when undertaking computational work. Lay description What is already known about the topic: Computational learning is an emerging area of school curricula; Limited research exists exploring thinking processes within computational learning; Early studies challenge more recent claims of thinking skill transfer from computational work. What this paper adds: Computational work supports a range of general and higher order thinking skills; Task design and teacher skills are critical to achieving higher order thinking outcomes from computational work; Computational work in teams can support collaborative, cooperative and self‐management key competencies. Implications for practice and/or policy: Findings broaden the base of empirical support for including computational work in school curricula; Coding provides an engaging means of exercising complex thinking skills and key competencies in students; The data methods used provide teachers with visible evidence of students' thinking processes during computational work.